Unmask the silent hearing loss: a study of audiological profile in children with chronic adenotonsillitis - Satish, Hosaagrahara Subbegowda; Abhilasha, Somashekhar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic adenotonsillitis results in obstruction of eustachian tube (ET) due to edema, by mechanical obstruction and the upper respiratory tract infection disrupts the mucocilliary action of ET which can lead to otitis media with effusion (OME). This when unresolved can result in persistent hearing loss and this might cause subsequent delay in development of language, social behaviour, learning difficulties which will affect the academic performance. Young children as are unable to voice their hearing loss and sometimes due to inattentiveness of parents to child’s hearing disorder; this might be neglected. The condition remains masked for a long time and hence need to be unmasked for its appropriate management. Methods: It is cross sectional study involving cases of chronic adenotonsillitis from November 2016 to May 2018. After enrolling the patients who met the inclusion criteria, their demographic details, examination findings including the findings of x-ray nasopharynx, pure tone audiometry (PTA) and tympanometry were noted for analysis. Results: Total 100 patients were studied in which history of hearing loss was seen in 23% and parents’ suspicions was in 22% of cases whereas hearing loss was demonstrated in 51% of cases using PTA ranging from 16-70 db in hearing level. Analyses of tympanogram revealed 43% to have either type B or type C tympanogram which are suggestive of OME. Conclusions: Audiological screening for children diagnosed with chronic adenotonsillitis needs to be made mandatory to detect OME, the silent hearing loss as parents as well as children will miss out on it.